Scottish highlands and the Atlantic world social networks and identities - Kehoe, S. Karly ca. 20./21. Jh; Dalglish, Chris; Tindley, Annie ca. 20./21. Jh (Edinburgh University Press, 2023)
Reveals the importance of social networks and identities to defining Highland Scots' engagements with Empire and its lasting legacies
Keywords: Scots / Great Britain / Colonies / History; Scots / Great Britain / History; Amerikanische Geschichte; Colonialism & imperialism; HISTORY / Americas (North, Central, South, West Indies); History of the Americas; Kolonialismus und Imperialismus; POL045000; SOCIAL SCIENCE / Slavery; Sklaverei und Abschaffung der Sklaverei; Slavery & abolition of slavery; Great Britain / Colonies / History; Britisches Empire; British Empire; Nordschottland, Highlands und Inseln; Northern Scotland, Highlands & Islands